Traditional banks, shadow banks and the US credit boom: Credit origination versus financing - Robert Unger (Deutsche Bundesbank, 2016)
The US credit boom has been identified as one of the causes of the global financial crisis and the resulting debt overhang is seen as the primary reason for the weak economic recovery. Most of the existing literature links the credit boom to the emergence of the shadow banking system. This paper shows that the largest part of the shadow banking system merely transforms existing financial claims against ultimate borrowers that have been originated by traditional banks. Based on financial accounts data, it is estimated that, shortly before the onset of the financial crisis, just about 12% of loans to the non-financial private sector had been originated by shadow banks. Consequently, dampening credit creation by the traditional banking sector might be an additional policy instrument to reduce the build-up of systemic risk in the shadow banking system.
Keywords: E40; E50; F30; G21; G23; 330; banks; credit boom; credit creation; financial crisis; shadow banks; systemic risk